Penurunan Kesadaran dan Kejang Berhubungan dengan Peningkatan Mortalitas pada Pasien Covid-19: Studi Retrospektif di Rumah Sakit Umum Dr. Sardjito Yogyakarta - Satiti, Sekar; Edyanto, Abdullah Syafiq; Pambudi Sejahtera, Desin; Nalendra Tama, Whisnu; Yuli Firlando, Afdhal; Vidyanti, Amelia Nur (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2023)
Introduction: Coronavirus infection has been associated with neurologic manifestations. Aim: The aim of this study was to investigate the predictors of mortality based on neurological manifestations among hospitalized COVID-19 patients. Methods: This was a retrospective study on COVID-19 patients hospitalized at Dr. Sardjito General Hospital Yogyakarta, Indonesia from March 9, 2020 to January 28, 2021. Demographic characteristics, medical history, symptoms, and clinical signs were extracted from medical records. Factors associated with the mortality were analysed using multivariate logistic regression analysis. Results: A total of 421 medical records were examined. Among them, 114 individuals died during hospitalization (27.08%). Several baseline characteristics were associated with mortality including age (OR: 1.05, 95%CI: 1.03-1.07, p = 0.000), history of diabetes mellitus (DM) (OR: 3.1, 95%CI: 1.95-4.95, p= 0.000), history of hypertension (OR: 1.88, 95%CI: 1.22-2.92, p= 0.004), and history of renal insufficiency (OR: 3.73, 95%CI: 2.2-6.32, p= 0.000). Neurological manifestation that associated with mortality were loss of consciousness (OR= 34.70, 95%CI: 12.67-95.05, p= 0.000), delirium (OR= 21.01, 95%CI: 3.85-114.51, p= 0.000), and seizure (OR= 31.01, 95%CI: 3.82-251.69, p= 0.001). On the multivariate analysis, loss of consciousness (OR: 33.10, 95%CI: 12.00-91.33, p= 0.000), and seizure (OR: 22.75, 95%CI: 2.16 to 239.81, p= 0.009) were independent predictive factors for mortality. Discussion: Loss of consciousness and seizure were neurological manifestations served as independent predictive factors for mortality in COVID-19 patients. Keywords: COVID-19, loss of consciousness, mortality, neurological manifestations, seizure